Implementasi Nilai Pancasila di Era Disrupsi Pada Proses Pembelajaran Anak Sekolah Dasar - Mita Maulani; Dinie Anggraeni Dewi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
This study aims to create and apply Pancasila values ​​to the country in line with the rapidly developing technological developments. This research method uses qualitative methods with literature methods. This research information is by reading several journals and books and finding out about the application of the value of Pancasila with this era of disruption. The results showed that in this era of disruption, the value of Pancasila needs to be implemented with the development of technology for elementary school children in Indonesia to continue to obey and live in accordance with applicable rules and not change its meaning. In implementing the Pancasila values, it is hoped that elementary school children will continue to love the nation and the country, have good morals, have noble character and have good manners.